A National Survey of Pediatric Intensive Care Units in Pakistan. (5th January 2014) - Haque, Anwarul; Ladak, Laila A.; Hamid, Muhammad H.; Mirza, Sadiq; Siddiqui, Naveed R.; Bhutta, Zulfiqar A.
Abstract : Purpose . To describe the structure, staffing resources, equipment, academic activities, and characteristics of pediatric population of pediatric intensive care units across the country. Material & Method . This was a prospective, descriptive, and observational survey of pediatric intensive care units from January to December 2009 across Pakistan. A questionnaire survey was emailed to director of each unit. Results . 16 PICUs were participated in this survey (100% response rate). A total of units with 155 beds were identified (1.1 bed /500, 000 children). Regarding the categories, 12 (75%) were medical, 3 (19%) were pure cardiac intensive care units, and one unit (6%) was combined multidisciplinary cardiothoracic unit. 13 (81%) units were in public sector as compared to 3 (19%) were in private sector. The mean unit size was 9.7 (range 4–28) beds. Twelve (75%) units were located in three large cities. Only 3 (19%) units have trained intensivist. 37% (6/16) had nurse to patient ratio of 1 : 1-1 : 2 while others had ratios of 1 : 3–1 : 5 with all nurses specialized trained for pediatric intensive care units with bachelor degree or diploma in nursing. Only 50% had capacity for invasive monitoring. Conclusion . We found inadequacies in several aspects of PICUs in Pakistan including fewer PICUs, inadequate PICU beds, and lack of trained personal to look after critically ill pediatric population.